Nekatere težave mladih prevajalcev pri prevajanju strokovnih besedil - primeri napak v prevodih komercialnega besedila - Dobnik, Nadja (Vestnik za tuje jezike, 2019)
The translation of authentic texts from economics and commerce is an important part of educating future professional translators. For most students, technical translation represents the first deviation from the general and literary languages, venturing into an area where they cannot resort to personal experience and have to trust resources and solutions they find foreign. The didactic function of specialized translation is rooted in the careful selection of authentic texts and a systematic review of student translations with error feedback. This allows students to grow conscious of the challenges of specialized translation as they experience first-hand that they need to not only comprehend the text, but also patiently and carefully look for the right resources, understand relations and contexts, and use precise target expressions. The article presents the results of an empirical study of student translations of the text "Conditions de vente" completed between 1999/2000 and 2014/2015. The results show issues and errors on multiple levels, for example with commercial expressions and idioms or the comprehension and translation of syntactic structures, as well as issues typical of students and young translators, such as insufficient general knowledge, inadequate text formation in Slovene, and insufficient persistence, precision and motivation to produce a suitable translation.
Keywords: analize napak; francoščina; komercialna besedila; slovenski študenti; slovenščina; strokovni jezik; strokovno prevajanje